PENGARUH PENGGUNAAN GAME EDUKASI EDUCANDY TERHADAP KEMAMPUAN GOI SISWA SMAN 6 PADANG - Muhammad Irvan; Rita Arni (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2023)
Numerous students consider it is challenging to master goi when learning Japanese, and the enormous amount of goi is one of the obstacles to learning Japanese. This study discovered that students find it challenging to master goi based on observations performed while conducting Educational Field Experience Practice (PPLK) at the Senior High School of 6 Padang and being interviewed by Japanese teachers. Due to students’ lack of enthusiasm and motivation in learning goi; thus, students did not have much ability to learn goi. Therefore, teaching media is necessary to engage students’ interest and facilitate their learning goi. The usage of educational media can overcome this issue. This study aimed to determine the effect of educational media on the ability of goi in tenth-grade students of Senior High School of 6 Padang. This study employed a quantitative and experimental design with a post-test control group design. The data collected comprised 72 sampled from tenth-grade students majoring in Mathematics and Natural Sciences 3 and Mathematics and Natural Sciences 2. Based on the findings of the independent sample t-test, it can be inferred that h1 was accepted at a sig. level was 0.0045<0.05, indicating that the goi ability of students in the experimental class is superior to that of students in the control class. In other words, the usage of educandy media affected the goi skills of tenth-grade students of Senior High School of 6 Padang.